Forest cover and fruit crop size differentially influence frugivory of select rainforest tree species in Western Ghats, India. (17th June 2020) - Gopal, Abhishek; Mudappa, Divya; Raman, T. R. Shankar; Naniwadekar, Rohit
Abstract: Forest fragmentation and habitat loss are major disruptors of plant–frugivore interactions, affecting seed dispersal and altering recruitment patterns of the dependent tree species. In a heterogeneous production landscape (primarily tea and coffee plantations) in the southern Western Ghats, India, we examined effects of surrounding forest cover and fruit crop size on frugivory of four rainforest bird‐dispersed tree species ( N = 131 trees, ≥30 trees per species, observed for 623 hr). Frugivore composition differed among the four tree species with the large‐seeded Canarium strictum and Myristica dactyloides being exclusively dependent on large‐bodied avian frugivores, whereas medium‐seeded Persea macrantha and Heynea trijuga were predominantly visited by small‐bodied and large‐bodied avian frugivores, respectively. Using the seed‐dispersal‐effectiveness framework, we identified effective frugivores and examined their responses to forest cover and fruit crop size. Results were idiosyncratic and were governed by plant and frugivore traits. Visitations to medium‐seeded Persea had a positive relationship with forest cover but the relationship was negative for the large‐seeded Myristica . In addition, two of the three effective frugivores for Persea responded to the interactive effect of forest cover and fruit crop size . Frugivore visitations to Heynea were not related to forest cover or fruit crop, and there were too few visitations to Canarium to discern any trends . These results highlight the context‐specific responses of plant–frugivore interactions to forest cover and fruit crop size influenced by plant and frugivore traits.